EKSISTENSI AMMATOA DALAM PEMERINTAHAN DESA TANAH TOWA KABUPATEN BULUKUMBA - Muhajir,; Hisbullah, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research aims to determine the comparison of the roles of the Kajang Ammatoa adat and the Village Head in the government of Tanah Towa village in Bulukumba district. The problem in this research is that there are differences in about the community regarding the position of highest power in the Tanah Towa Village Government between the Traditional Head and the Village Head. This research uses a type of qualitative research using an empirical normative approach. The data collection methods used in this research are observation, interviews, literature and documentation. The results of the research show that the existence of Ammatoa in the Tanah Towa village government, Bulukumba Regency, if compared with the village head, is the traditional head's presence is more existent, because until now he still holds firmly to the name of Pasang Ri Kajang, one of which is that they want the area not to be contaminated with foreign culture. . Ammatoa plays a role in managing the indigenous community as an elder for the entire Kajang Ammatoa indigenous community. Meanwhile, village heads prefer areas outside customary areas because of the existing customary regulations or Pasang Ri Kajang (laws).